Profiting without producing: how finance exploits us all - Lapavitsas, Costas (London, 2013)
"Financialization is one of the most innovative concepts to emerge in the field of political economy during the last three decades, although there is no agreement on what exactly it is. "Profiting Without Producing" puts forth a distinctive view defining financialization in terms of the fundamental conduct of non-financial enterprises, banks and households. Its most prominent feature is the rise of financial profit, in part extracted from households through financial expropriation. Financialized capitalism is also prone to crises, none greater than the gigantic turmoil that began in 2007. Using abundant empirical data, the book establishes the causes of the crisis and discusses the options broadly available for controlling finance."